민간보험가입여부가 한방의료이용에 미치는 영향요인 -2014년 한방의료이용 및 한약소비실태조사(보건복지부)를 중심으로 - 성안젤라동민; 박해모; 이선동; Sung, Angela Dongmin; Park, Haemo; Kim, Hyundo; Lee, Sungdong (대한예방한의학회지, 2017)
Objectives : The purpose of this study was to analyze the report conducted in 2014 by the Ministry of Health and Welfares on influences of private insurance coverage on the use of Korean medicine. Methods : We analyzed Ministry of Health and welfares report on the use and consumption of Korean medicine to fit the purpose of this study. Comparison between private insurance holders and non-holders was made in the areas of sociodemographic characteristics, patient distribution by disorders, total number of disorders and existence of complex diseases, general perception of Korean medicine, and medical expenses and visits. Logistic regression analysis was made to verify the private insurance coverage. Results : Among sociodemographic characteristics, significant differences were observed in age distribution, education, professions, income level, and housing factors. But genders, area of residence, and marital status didn't show significant differences. Other significant differences including side effects, experience with Korean medicine, herbal medicine and acupuncture treatments, and main visiting facilities were shown between private insurance holders and non-holders. Majority of disorders treated with Korean medicine were musculoskeletal issues, and criteria of number of disorders, multiple diseases factors, and medical expenses/visits showed significant differences between the two groups. Conclusions : Summarizing above results indicate that holding a private insurance in addition to National Health Insurance contributes significant influences on the use of Korean medicine.